THE OPINION ABOUT THE RATING SYSTEM IN NATIONAL RESEARCH UNIVERSITY - Evgeniy A. Kharitonov; Oleg V. Mikhaylov; Nataliya E. Kharitonova (Высшее образование в России)
The article views the general methodology for objective evaluation of scientificand pedagogical activity of teaching personnel in higher education institutions with the status of «national research university». This methodology is based on a ranking system for estimation of actual work performed by a lecturer in his professional duties. It has been noted that despite of its relative complexity, it generally seems to be quite acceptable for implementation at institutions of higher education of the above categories.